Supporting data for “Clusterin as a functional downstream target in Sox9-expressing hepatocellular carcinoma”. - Pik Ying Wong; Cheuk Lam Regina Lo (HKU Data Repository, 2020)
Hepatocellular
carcinoma (HCC) is one of the deadliest cancers across the globe. Patients are
usually diagnosed at advanced stage. Presence of microvascular metastasis,
oversized tumor burden and insufficient liver remnant reduce the feasibility to
surgical and local ablative treatment modalities. Besides, high propensity of
tumor recurrence and metastasis increase the level of challenge in eliminating
HCC. As a matter of fact, targeted therapy confers survival benefits to HCC
patients in late phase. In this regard, elucidating the genetic events that
underlies HCC is of the utmost importance to supply potential biomarkers for
HCC detection and druggable targets for curative purpose.
As
a transcription factor, Sox9 masters embryogenesis and sexual development.
Emerging evidence illustrated that Sox9 overexpression facilitates tumor
initiation and progression in multiples solid cancers. Sox9 overexpression is
associated with aggressive behavior. Of note, Sox9 is a stem cell factor which
endows stemness properties in cancers. Based on our previous study, knocking
down Sox9 inhibited cell growth, cell migration and invasion, but enhanced
chemosensitivity. Apart from this, decline of Sox9 expression suppressed the
expression of stemness markers and tumorsphere formation ability. The oncogenic
potential of Sox9 was mediated by Wnt signaling pathway via transcription
regulation of Frizzled-7. To further dissect the molecular mechanism underlying
Sox9-expression HCC, we tried to identify the molecular target from cancer
secretome regulated by Sox9. Furthermore, its functional role and clinical
significance were evaluated.
To
this end, the HCC secretome upon Sox9 silencing in HCC cell lines was examined
by mass spectrometry. Our results revealed Clusterin (CLU) was a commonly
downregulated in the conditioned medium (CM) from Sox9 knockdown clones
compared with the control. A high serum CLU level was correlated with advanced
HCC stages. Moreover, CLU could better differentiate tumor stages and predict
clinical outcomes when used in combination with serum alpha-fetoprotein (AFP)
level. After investigating the clinical features of CLU, we further explored
the oncogenic potential of Sox9-CLU axis using in vitro assays. Through cell
migration and invasion assays, CM from Sox9 knockdown clones retarded cell
migration ability and invasiveness. Conversely, addition of CLU recombinant
proteins enhanced cell motility in the transwell assays. Enhanced cell
migration and invasion induced by Sox9 overexpression could be abrogated by the
use of neutralizing CLU antibody which reduced extracellular CLU expression. By
predictive analysis, Sox9 putative binding sites were identified in the
promoter region of CLU. The binding interaction was validation by chromatin
immunoprecipitation (ChIP) assay.
In
summary, findings from this study suggests that CLU is a downstream effector in
the secretome of Sox9-expressing HCC. Targeting secreted CLU may present a
novel therapeutic strategy to improve the disease outcome of Sox9-expressing
HCC.
Keywords: 111201 Cancer Cell Biology